Synergistic effect of particle packing method, aggregate saturation levels, and paste content in improving the performance of high volume fine recycled aggregate concrete - Namratha V. Khanapur; Bhavna Tripathi; Subhasis Pradhan; Tarush Chandra (Scientific Reports)
Abstract Using fine recycled concrete aggregate (FRCA) is challenging because of the presence of mortar fines in higher quantities. Past studies have reported a few approaches (Presoaking FRCA, surface treatment of FRCA, use of mineral admixture, method of mix proportioning, and mixing FRCA concrete) to improve the performance of FRCA concrete. However, these studies recommend the deployment of 30–50% FRCA as a substitute for natural fine aggregate. Additionally, the treatment methods are not cost-effective. To address these limitations and upscale the use of FRCA, this study introduces the particle packing method (PPM) for mix proportioning, a modified presoaking method for concrete mixing, and presents the effect of aggregate saturation level and paste content on the performance of concrete. Concrete mixes with 0–100% FRCA, 15% and 20% extra paste contents, and different aggregate saturation levels (50–100%) were prepared. The mechanical and durability properties of concrete, such as compressive strength, flexural strength, modulus of elasticity, abrasion resistance, sorptivity, water permeability, and chloride ingress, were analysed by replacing 0–100% crushed stone sand (CSS) with FRCA. The initial results showed a significant reduction in the mechanical and durability properties of fully saturated 100% FRCA concrete than the control mix. However, substantial improvement was seen by using partially saturated (50%) FRCA, and 20% paste content. The effect of decreasing FRCA saturation level was prominent. On using 50% saturated FRCA, the compressive strength, flexural strength, static and dynamic modulus of elasticity, and abrasion resistance, improved by 16%, 14%, 14%, 8%, 13%; and exhibited a lower sorptivity, water permeability, and chloride ingress of 56%, 14%, and 34%, respectively. The microstructural analysis showed that by reducing the saturation level and increasing the paste content a denser interfacial transition zone can be obtained. Furthermore, using PPM for mix proportioning is beneficial in minimizing the cement content for FRCA concrete mixes. The study demonstrates the synergistic effect of the PPM mix proportioning method, modified mixing method, 20% extra paste content, and partially (50%) saturated FRCA in improving the performance of untreated high-volume FRCA concrete, thereby supporting a sustainable approach.